Cervical funneling as a predictor of successful induction of labor in term pregnancies - Reyna-Villasmil, Eduardo (2024)
Objective: To evaluate the usefulness of cervical funneling as a predictor of successfullabor induction in term pregnancies. Design: Case-control study. Institution: HospitalCentral de Maracaibo, Venezuela. Participants: Pregnant women who underwentlabor induction. Methods: Pregnant women were evaluated by ultrasound toestablish the presence or absence of cervical tunneling before the start of laborinduction. Main outcome measures: Maternal characteristics, induction-deliveryinterval and type of delivery. Results: A total of 443 pregnant women who underwentinduction or labor were selected. Cervical ultrasound evaluation revealed that 192patients (44.3%) displayed cervical funneling. No statistically significant differenceswere observed between the two groups in general characteristics (p = ns). Inpatients with cervical tunneling, the induction and delivery onset interval was 14.2± 5.5 hours, while in those without it was 16.0 ± 5.0 hours (p = 0.0004). As for modeof delivery, patients with tunneling had 168 deliveries (87.5%) compared to 181deliveries (72.1%) in group B (p < 0.0001). On the other hand, 67 deliveries (34.8%) inthe cervical tunneling group occurred within 12 hours after induction, while patientswithout cervical tunneling recorded 66 deliveries (26.2%) in the same period (p =0.0497). Conclusion: The findings of this investigation suggest that cervical tunnelingis a useful predictor for successful induction of labor in term pregnancies.